MULTI SLICE CT ANGIOGRAPHY - Hafizullah, Muhammad (Journal of Postgraduate Medical Institute, 2011)
With the advent of new technology and sophistication of equipment, visualisation of coronary arteries and peripheral vessels in the body has become a reality without introducing catheters. CT scan opened a new window offering unrestricted views of many vital structures of body. It has helped in unravelling diagnosis in structures in thorax and abdomen besides brain. However heart and vessels, so far, eluded this technology. Heart is a restless organ and its motion is complex as it squeezes, contracts, moves clockwise and axially at the same time. Coronary arteries of different calibres run on the surface of heart in different directions. Besides motion of heart, chest moves with respiration. Ultra fast technology is required to freeze the heart motion at several frames and then reconstruct especially to image small coronary arteries.